Tissue factor: an enzyme cofactor and a true receptor - Morrissey, J H (Thrombosis and haemostasis, 2001)
Tissue factor is considered to be the physiologic trigger of the blood clotting system in normal hemostasis and in many--perhaps most--thrombotic diseases. A wealth of new knowledge is available regarding the structure and assembly of the TF:VIIa complex and the role of factor VIIa and tissue factor in hypercoagulable states. The exciting recent finding that tissue factor can function as a signaling receptor, and suggestions that tissue factor may have important, non-hemostatic roles, will be the subject of much additional study in the near future.